Ecopolitics Podcast, Episode 13: Corporate Sustainability in Canada - Katz-Rosene, Ryan; Andrée, Peter (Université d'Ottawa | University of Ottawa, 2020)
In this episode we get real about corporate social responsibility, or what Rory MacAlpine of Maple Leaf Foods calls his company's "shared value" for all its stakeholders. [Produced by Nicole Bedford; Artwork by Adam Gibbard; Transcription by Allison Brown; Additional Resources prepared by Ashley Fearnall].